A CLINICAL STUDY TO EVALUATE THE COMBINED EFFECT OF KESHARSIDDHA GHRIT NASYA AND YOG BASTI ALONG WITH TAB. PATHYADI GHANVATI IN ARDHAVBHEDAKA W.S.R. TO MIGRAINE - Salunke Amrut; Kranti Kendre (International Journal of Ayurveda and Pharma Research, 2019)
Migraine is the disease of recurrent attack of headache which usually involves half of head. It is felt as throbbing type of pain and associated with various symptoms like, Nausea, vomiting, Photophobia etc. Its acute attacks are treated with different analgesics or ergotamine preparations. A modern medicine gives instant relief from symptoms but may cause drowsiness, insomnia, depression etc.As compare to that, Ayurveda has variety of natural plant medication and Panchakarma therapeutic procedures in management of Ardhavabhedaka. Thus, the study was selected to evaluate the efficacy of Ayurvedic Panchakarma therapy in migraine. The duration of the treatment was 30 days. Out of 17 migraine patients who were offered this Ayurvedic treatment, 12 patients completed total 30 days treatment protocol. Detail history and examination of each patient were done. Kesharsiddhaghrit Nasya and Dashmul kwath yog basti given along with Tab. Pathathyadi Ghanvati.Evaluation was done. Total disappearance of headache and associated symptoms at completion of treatment was observed in 66.66% patients. Mild episode of headache without need of any regular treatment was observed in 8.33% of patients. Low intensity of pain along with their regular treatment was observed in 16.66% of patients. Very mild improvement in 8.33% patients and no worst pain was noted in a single patient during treatment (0.0%); respectively. From the results and observation obtained from this study it can be concluded that Ayurvedic Panchakarma therapy showing better results in Ardhavabhedaka. No any harmful side effects were found during this entire study.